2023
DOI: 10.1186/s12874-023-01846-3
|View full text |Cite
|
Sign up to set email alerts
|

When a joint model should be preferred over a linear mixed model for analysis of longitudinal health-related quality of life data in cancer clinical trials

Abstract: Background Patient-reported outcomes such as health-related quality of life (HRQoL) are increasingly used as endpoints in randomized cancer clinical trials. However, the patients often drop out so that observation of the HRQoL longitudinal outcome ends prematurely, leading to monotone missing data. The patients may drop out for various reasons including occurrence of toxicities, disease progression, or may die. In case of informative dropout, the usual linear mixed model analysis will produce b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Our findings were consistent with prior studies. First, most of the previous studies on joint models, both linear and nonlinear, showed that joint models outperformed separate models in the presence of informative dropout [2428, 30, 32], which was consistent with our key findings. Second, the mix-effects model in the separate models that ignored informative dropout showed over-optimistic estimates for the disease progression trend, corresponding to conclusions drawn in previous studies [2628].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings were consistent with prior studies. First, most of the previous studies on joint models, both linear and nonlinear, showed that joint models outperformed separate models in the presence of informative dropout [2428, 30, 32], which was consistent with our key findings. Second, the mix-effects model in the separate models that ignored informative dropout showed over-optimistic estimates for the disease progression trend, corresponding to conclusions drawn in previous studies [2628].…”
Section: Discussionsupporting
confidence: 91%
“…First, most of the previous studies on joint models, both linear and nonlinear, showed that joint models outperformed separate models in the presence of informative dropout [2428, 30, 32], which was consistent with our key findings. Second, the mix-effects model in the separate models that ignored informative dropout showed over-optimistic estimates for the disease progression trend, corresponding to conclusions drawn in previous studies [2628]. It was shown that subjects who dropped out due to excessively high or low longitudinal measures were downweighed during the estimation procedure, so they contributed weakly to the likelihood function in the mixed-effects models.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations